BETWEEN A RELIC OF THE PAST AND A SOCIALIST DUTY: CHILD AND ADOLESCENT LABOUR IN ‘COMUNIST POLAND’ IN THE LIGHT OF LITERARY FICTION FOR YOUNG PEOPLE (1948–1980) - Skrukwa, Grzegorz (Studia historiae oeconomicae, 2023)
this paper examines the cultural image of child and adolescent labour performed in the People’s Republic of Poland in the years 1948–1989 as was presented in the literary fiction addressed to the young people. During the Stalinist period, literature officially con- demned child labour on individual farms, but affirmed the labour of adolescent workers in state industry and construction. After the 1956 Thaw, the subject matter of labour was re- ceding into the background, for several reasons. Nevertheless, the post-1956 youth litera- ture also featured labour-related themes: community works, school cooperatives, work in family crafts, tutoring, and shady trade.